Assessment of Pandemic and Seasonal Influenza A (H1N1) Virus Susceptibility to Neuraminidase Inhibitors in Three Enzyme Activity Inhibition Assays - Nguyen, Ha T. (American Society for Microbiology (ASM), 2010)
The neuraminidase inhibitors (NAIs) zanamivir and oseltamivir are currently the only antiviral drugs effective for the treatment and prophylaxis of 2009 pandemic influenza A (H1N1) virus infections. The proven potential of these viruses to acquire NAI resistance during treatment emphasizes the need to assess their NAI susceptibility. The 50% inhibitory concentrations (IC(50)s) are known to vary depending on the neuraminidase inhibition (NI) test used; however, few side-by-side comparisons of different NI assays have been done. In the present study, a panel of 11 isolates representing 2009 seasonal and pandemic influenza H1N1 viruses, including oseltamivir-resistant H275Y variants, were tested in three functional NI assays: chemiluminescent (CL), fluorescent (FL), and colorimetric (CM). The sensitivities of the viruses to zanamivir, oseltamivir, and three investigational NAIs (peramivir, R-125489, and A-315675) were assessed. All isolates with the exception of H275Y variants were sensitive to all five NAIs by all three NI assays. The H275Y variants showed substantially elevated IC(50)s against oseltamivir and peramivir. The three NI assays generally yielded consistent results; thus, the choice of NI assay does not appear to affect conclusions based on drug susceptibility surveillance. Each assay, however, offers certain advantages compared to the others: the CL assay required less virus volume and the FL assay provided the greatest difference in the IC(50)s between the wild type and the variants, whereas the IC(50)s obtained from the CM assay may be the most predictive of the drug concentrations needed to inhibit enzyme activity in humans. It would be desirable to develop an NI assay which combines the advantages of all three currently available assays but which lacks their shortcomings.